A novel design to produce high-strength and high-toughness alumina self-lubricated composites with enhanced thermal-shock resistance—Part I: Mechanical properties and thermal shock behavior of Al2O3/Mo-Al2O3 laminated composites. Issue 1 (January 2017) - Song, Junjie; Su, Yunfeng; Fan, Hengzhong; Zhang, Yongsheng; Hu, Litian
Abstract: This paper proposes a new strategy to design the high-performance Al2 O3 /Mo self-lubricated composites with excellent practical value and durability. The relationships among the relevant structural parameters, interfacial compositions, mechanical and thermal properties of the materials were analyzed. Results show that the apparent toughness, bending strength and work of fracture of the optimal Al2 O3 /Mo-Al2 O3 laminated materials could reach 8.1 MPa m 1/2, 634 MPa and 330 J m −2 . Moreover, the new-developed materials exhibited a good self-lubricating property on every surface and thermal shock resistance. The friction coefficients of all the surfaces can be as low as 0.45 at 800 °C, and the retention rates of strength and toughness after thermal shock between 25 °C and 1000 °C for 50 cycles could reach 98.8% and 85.3%, respectively. The new strategy is based on a combination strong interfacial bonding and with accelerated formation of a reasonable residual stress and enhanced grain-interlocking among particles during fatigue.